Adapting roughages varying in quality and curing processes to the nutrition of beef cattle. Pelleted alfalfa hay and dehydrated pelleted green forage-type sorghum in the winter ration of heifer calves - Smith, E.F.; Koch, B.A.; Richardson, D.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This is the second year of an experiment designed to compare the feeding value of alfalfa fed as long hay or coarsely-ground hay pellets, and forage-type sorghum fed as silage or dehydrated green forage sorghum pellets. Fifty head of choice-quality heifer calves from the Jeff Ranch, Fort Davis, Texas, were used in this experiment. They were allotted, 10 head per lot, on the basis of live weight, and fed a winter ration.
Keywords: Beef; Quality; Curing; Pelleted alfalfa hay